Awareness of nutrition and health knowledge and its influencing factors among Wuhan residents - Yating Wu; Shanshan Wang; Mengdie Shi; Xinzheng Wang; Hongjuan Liu; Shu Guo; Le Tan; Xuefeng Yang; Xiaomin Wu; Liping Hao (Frontiers Media S.A., 2022)
BackgroundNutrition and health knowledge play a crucial role in promoting healthy dietary behaviors, and have been found to be related to sociodemographic characteristics. However, the existing evidence is limited and inconsistent. We aimed to evaluate the awareness level of nutrition and health knowledge and its influencing factors among Wuhan residents, and to provide scientific basis for carrying out targeted nutrition education programmes.MethodsBy stratified random sampling, residents aged 18-64 in Wuhan were selected for self-administered questionnaire survey. We adopted the structured questionnaire to investigate respondents' sociodemographic characteristics, nutrition and health knowledge, and the way to acquire knowledge. Among them, nutrition and health knowledge includes the following four parts: dietary guidelines recommendations, food and nutrients, nutrition and disease prevention, and nutrition skills. Chi-square tests were used to analyze the associations between total awareness rate and sociodemographic characteristics. Multiple linear regression models were used to analyze the influencing factors of nutrition and health awareness.ResultsA total of 33,436 valid questionnaires were obtained, with a response rate of 97.8%. The total awareness rate was 20.4%, with the highest in nutrition and disease prevention (72.7%) and the lowest in nutrition skills (46.3%). Responders aged 35-44 (23.3%), females (22.8%), educational workers (24.8%), obtaining a master's degree or above (34.1%), living in downtown area (23.1%), and without a history of chronic disease (24.6%) were more likely to have higher awareness rates (all p < 0.001). The multiple linear regression models showed that age, gender, education level, occupation, residential address, and the history of chronic disease were the potential factors affecting individual nutrition awareness.ConclusionThe total awareness rate of nutrition and health knowledge among Wuhan residents was not optimistic. Besides, our findings suggested that sociodemographic characteristics are closely related to nutrition awareness, which may provide important clues for carried out nutrition education campaigns.